Handbook of research on energy-saving technologies for environmentally-friendly agricultural development - Kharchenko, Valeriy 1938-; Vasant, Pandian 1961- (IGI Global, 2020)
"This book examines the research and development of new technologies and effective technical means to solve the problem of energy consumption decrease in the agricultural industrial sector and in the housing and communal services sector in the countryside"--Provided by publisher
Keywords: Agriculture / Energy consumption; Rural development